A 10+10+30 radio campaign is associated with increased infant vaccination and decreased morbidity in Jimma Zone, Ethiopia: A prospective, quasi-experimental trial - Bernard Appiah; Lakew Abebe Gebretsadik; Abebe Mamo; Brittany Kmush; Yisalemush Asefa; Christopher R. France; Elfreda Samman; Tena Alemayehu; Mahdiya Abafogi; Md Koushik Ahmed; Laura Forastiere; Gursimar Kaur Singh; et al. (Public Library of Science (PLoS), 2022)
Mass media interventions have the potential to reach large audiences and influence health behaviours and outcomes. To date, no study has evaluated the effect of a radio-only campaign on infant vaccination coverage, timeliness, and related morbidity in a low-income country. We implemented the "10+10+30" radio campaign involving broadcasting a weekly 10-minute radio drama series on vaccination, followed by a 10-minute discussion by community health workers, and then a 30-minute listener phone-in segment in Jimma Zone, Ethiopia for three months. To assess the impact of 10+10+30, which was aired on a community radio station, we recruited mothers of infants up to 5 weeks old in intervention district clusters that were inside the radio station's reception range (n = 328 dyads) and control district clusters that were outside of the range (n = 332 dyads). Intention-to-treat and per-protocol analyses, adjusted for pre-intervention differences between the districts, were conducted to examine the co-primary outcome of Penta-3 vaccination coverage and timeliness as well as those of other vaccines and outcomes related to infant morbidity. Both intention-to-treat and per-protocol analyses revealed higher vaccine coverage (p<0.001) and more timely vaccine administration (p<0.001) in the intervention district relative to the control district, with infants in the intervention district being 39% more likely to receive a Penta 3 vaccination (adjusted RR: 1.39, p<0.001). In addition, adjusted regression analyses of maternal retrospective reports over a two-week period revealed 80% less infant diarrhoea (RR: 0.20, p<0.001), 40% less fever (RR: 0.60, p<0.001) and 58% less cough (RR: 0.42, p<0.001) in the intervention district relative to the control district. This study provides compelling initial evidence that a radio drama integrated with discussion and phone-in components may improve infant vaccination coverage and timeliness, and may reduce infant morbidity. Randomized controlled trials are needed to confirm and extend these findings with other samples.